2013
DOI: 10.1007/s11064-013-1199-5
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to the Metabolic Pathways and Function of Metabolites Observed in Human Brain 1H Magnetic Resonance Spectra

Abstract: The current knowledge of the normal biochemistry of compounds that give rise to resonances in human brain proton magnetic resonance spectra measureable at readily available field strengths (i.e. ≤3 T) is reviewed. Molecules covered include myo- and scyllo-inositol, glycerophospho- and phospho-choline and choline, creatine and phosphocreatine, N-acetylaspartate, N-acetylaspartylglutamate, glutamate, glutamine, γ-aminobutyrate, glucose, glutathione and lactate. The factors which influence changes in the levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
578
6
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(616 citation statements)
references
References 441 publications
23
578
6
9
Order By: Relevance
“…However, increased Glx in right frontal WM early in the illness could directly affect axons and result in NAAc reductions. 47 Overall, our findings are consistent with an NMDAR hypofunction process of glutamatergic sub-lethal excitotoxicity in GM and WM, which progresses but without neuronal loss. Effective antipsychotic treatment probably reduces glutamatergic turnover but not enough to completely arrest the underlying process.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, increased Glx in right frontal WM early in the illness could directly affect axons and result in NAAc reductions. 47 Overall, our findings are consistent with an NMDAR hypofunction process of glutamatergic sub-lethal excitotoxicity in GM and WM, which progresses but without neuronal loss. Effective antipsychotic treatment probably reduces glutamatergic turnover but not enough to completely arrest the underlying process.…”
Section: Discussionsupporting
confidence: 85%
“…Early in the illness we find an increase in Glx in GM and WM, consistent with greater glutamatergic turnover. 47 Later in the illness this process remains, but additional differential tissue-specific changes occur: in GM, higher NAAc suggestive of neuronal compaction 47 ; in WM, reduced NAAc and total-creatine, suggestive of axonal dysfunction and altered energy metabolism, respectively. Longitudinal GM (0.6%/y) and WM (0.3%/y) volume reductions (which decrease with age) have been documented in schizophrenia 8 as well as in un-affected twins, 48 suggestive of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…These correlations are illustrated in Figure 4. Because choline is present in higher concentrations in WM than GM (Rae, 2014) and tissue composition correlated with age and hearing loss, we repeated significant correlation analyses after partialing out age, hearing loss, and all tissue fractions from both RAC choline concentration and the subject variable of interest. It should be kept in mind that such extensive partialization removes a lot of variance from the data, so the same strength of correlation Table 1.…”
Section: Choline Spectroscopymentioning
confidence: 99%
“…Therefore, GABA deficiency may underlie excessive sound-evoked (Gu et al, 2010) and spontaneous (Adjamian et al, 2012) activity that has been observed previously in tinnitus in humans, even after matching for hearing loss and hyperacusis. However, GABA systems may have a more complex role in tinnitus; a recent study found evidence of increased GABAmediated tonic inhibition in the auditory thalami of rats with noise-induced tinnitus (Sametsky et al, 2015). This excess inhibition was in turn linked to abnormal burst firing of thalamic neurons, which has been argued to trigger abnormal cortical activity linked to tinnitus (Llinás et al, 1999).…”
Section: Gaba In Tinnitusmentioning
confidence: 99%
“…For example, the accumulation of 18 F-labeled 3,4-dihydroxy-6-[18F]fluoro-L-phenylalanine ([ 18 F]F-DOPA) in the brain measured with PET can be used as a quantitative index of dopamine synthesis capacity (Nanni et al, 2007;Pretze et al, 2014 (Rae, 2014). These include glutamate, glutamine, glutamate + glutamine (Glx), creatine (Cr), myo-inositol (Myo), and N-acetyl-aspartate (NAA), among several others (Rae, 2014).…”
Section: Introductionmentioning
confidence: 99%